2018
DOI: 10.1089/hum.2017.032
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Knockout ofCXCR4andCCR5Genes in CD4+ T Cells via CRISPR/Cas9 Confers Resistance to Both X4- and R5-Tropic Human Immunodeficiency Virus Type 1 Infection

Abstract: Previous research has proven that disruption of either the CCR5 or the CXCR4 gene confers resistance to R5-tropic or X4-tropic human immunodeficiency virus type 1 (HIV-1) infection, respectively. However, the urgent need to ablate both of the co-receptors in individual post-thymic CD4+ T cells for dual protection remains. This study ablated the CCR5 and CXCR4 genes in human CD4+ cell lines and primary CD4+ T cells simultaneously using clustered regularly interspaced short palindromic repeats (CRISPR)/Cas9, a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 53 publications
2
76
0
3
Order By: Relevance
“…This may be part of a more complex regulatory loop in which TGF-β induces adipocyte secretion of miR-130b, which is then transferred to muscle, where it acts to reduce the expression of PGC-1α, reducing muscle oxidative metabolism (202). Skeletal muscle is also responsive to miR-27a, which is present in adipose-derived exosomes and induces insulin resistance via PPARγ repression (203). Serum levels of miR-27a are positively associated with obesity and insulin resistance in children and in mice with obesity, indicating that miR-27a may be another modulator of obesity-associated insulin resistance (203).…”
Section: Review Series: Mechanisms Underlying the Metabolic Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…This may be part of a more complex regulatory loop in which TGF-β induces adipocyte secretion of miR-130b, which is then transferred to muscle, where it acts to reduce the expression of PGC-1α, reducing muscle oxidative metabolism (202). Skeletal muscle is also responsive to miR-27a, which is present in adipose-derived exosomes and induces insulin resistance via PPARγ repression (203). Serum levels of miR-27a are positively associated with obesity and insulin resistance in children and in mice with obesity, indicating that miR-27a may be another modulator of obesity-associated insulin resistance (203).…”
Section: Review Series: Mechanisms Underlying the Metabolic Syndromementioning
confidence: 99%
“…Skeletal muscle is also responsive to miR-27a, which is present in adipose-derived exosomes and induces insulin resistance via PPARγ repression (203). Serum levels of miR-27a are positively associated with obesity and insulin resistance in children and in mice with obesity, indicating that miR-27a may be another modulator of obesity-associated insulin resistance (203).…”
Section: Review Series: Mechanisms Underlying the Metabolic Syndromementioning
confidence: 99%
“…Our group also reported that disruption of the CXCR4 co-receptor by CRISPR-Cas9 resulted in protection of primary CD4 + T cells from HIV-1 infection [ 37 ]. However, to date, only one study has investigated simultaneous CXCR4 and CCR5 modification using CRISPR-Cas9, which was reported to inhibit HIV-1 infection in cells [ 38 ]. In this study only one combination of CXCR4 and CCR5 sgRNA was assessed.…”
Section: Introductionmentioning
confidence: 99%
“…As expected, CRISPR-Cas9-mediated knockout of the CCR5 gene inhibited HIV-1 infection in induced pluripotent stem cell-derived monocyte/macrophages [237], primary CD4+ T cells [238], and in vivo [239,240]. Similarly, CXCR4 knockout was shown to confer resistance to X4-tropic virus infection [241][242][243]. However, in view of the importance of CXCR4 in the development of hematopoietic cells [244], the clinical feasibility of this latter knockout approach is more problematic.…”
Section: Crisprmentioning
confidence: 70%